Efektivitas Pelaksanaan Mutasi Pegawai Badan Kepegawaian Daerah (BKD) - Takwim, Takwim; Ansar, Tahmit (Jurnal Ilmiah Dikdaya, 2022)
The effectiveness of the implementation of employee transfers at the Regional Civil Service Agency of Konawe Regency, shows that the placement of employees is still not appropriate when viewed from the composition of employees, clearly not based on educational background, this is certainly contrary to the principle of the right man in the right place, namely the placement of the right person in the right place. . In addition, the placement of employees here is also considered not objective because they are placed on the basis of work experience without looking at the competence and background of the employee. Of course it requires human resources with an educational background in civil engineering, where this agency is engaged in the construction of road and bridge spatial planning, but the work is carried out by people who are not suitable, the results will not run optimally. Thus, the assigned mutation employees have been able to even increase productivity in accordance with the main tasks and functions of each employee's work unit. Civil servants with mutations in the Regional Personnel Agency are said to have been able to adapt to their new jobs, especially in the administrative field, but the placement of Civil Service Civil Servants in the technical field of adaptation takes 1 to 6 months especially for Civil Servants who do not have basic skills in this field. As a transfer employee, the Civil Servant assigned to this new work unit admits that being placed in a new job can clearly eliminate employee boredom and boredom towards work, especially with the implementation of a transfer, PNS can improve employee career paths as an effort to improve careers higher.